Cultural identity as a factor in the competitiveness of gastronomic projects in a multinational environment - Lytvynenko, Kostiantyn (Актуальні питання економічних наук, 2025)
In today’s globalized society, gastronomy ceases to be just a sphere of consumption and gains importance as a cultural code, a means of communication, and a tool for representing identity. In a multinational environment, authentic gastronomic practices face the challenges of standardization, commercialization, and the need for cultural adaptation. In this context, cultural identity increases as a factor in preserving traditions and forming a unique market offer that can ensure the competitiveness of a gastronomic project at the local and international levels. The article aims to substantiate the role of cultural identity as a strategic resource for the competitiveness of gastronomic projects in a multicultural environment by analyzing its content, methods of representation, and perception by consumers, as well as studying practical models of its effective use in branding and positioning. Methods. The study used an interdisciplinary approach that combines methods of cultural analysis, content analysis, comparative analysis of brands of gastronomic projects, and generalization of scientific sources on gastronomic marketing and socio-cultural anthropology. Results. As a result of the study, it was found that cultural identity in the field of gastronomy performs not only a symbolic, but also an economic function: it contributes to the formation of a differentiated offer, the creation of emotional attachment of consumers to the brand, and increases its trust. A multicultural environment has proven to influence the reception of authentic gastronomic concepts, forming a demand for a combination of the local and the universal. Based on the analysis of the practices of regional and global projects, effective models of integrating cultural identity into brand communication strategies and the organization of gastronomic space have been identified. Conclusions. The study's results confirm that cultural identity acts as a means of preserving gastronomic heritage and an effective branding tool in a multicultural environment. Adapting traditional elements to the expectations of different target audiences strengthens gastronomic projects' competitiveness and contributes to the development of gastronomic tourism. At the same time, further scientific research should focus on developing applied models of communication of authentic cultural meanings in the globalized consumer space.